A high-efficiency power amplifier integrated with a planar transmitting antenna. - Prévost, Jean-Paul L. (University of Ottawa (Canada), 2001)
In this thesis, the coplanar-waveguide-fed aperture-coupled patch antenna is studied for the purpose of integration with a high efficiency power amplifier. A high efficiency power amplifier is designed via experimental determination of the loads required at the output of a transistor in order to maximise its efficiency. For this purpose, an active multi-harmonic load-pull system capable of independently varying the fundamental-frequency, second-harmonic-frequency and third-harmonic-frequency reflection coefficients seen at the output of a transistor is constructed. Six-port reflectometers are designed and validated for use in this application. The load-pull system's performance is also verified prior to designing the amplifier. A power amplifier is then designed to operate at 3.5 Ghz with an input power of 4mW. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.